2006
DOI: 10.1039/b606131a
|View full text |Cite
|
Sign up to set email alerts
|

Lattice strain effects on CO oxidation on Pt(111)

Abstract: Surface strain plays a major role in determining the rate limiting step and catalytic activity of platinum for CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 41 publications
(53 reference statements)
8
85
0
1
Order By: Relevance
“…Numerous works inspired by these early results demonstrated and utilized the effect of lattice strain in other metal catalyst systems, including gold, 20 , 23 platinum, 15 copper, 24 nickel, 25 and dealloyed bimetallic nanoparticles. 26 By surface chemistry measurements and theoretical calculations, Strasser and co-workers provided a molecular level understanding of the unprecedented electrocatalytic activity for the electroreduction of oxygen on dealloyed fuel cell catalysts.…”
Section: Eff Ect Of Strain On Reactivity Of Metal Surfacesmentioning
confidence: 99%
“…Numerous works inspired by these early results demonstrated and utilized the effect of lattice strain in other metal catalyst systems, including gold, 20 , 23 platinum, 15 copper, 24 nickel, 25 and dealloyed bimetallic nanoparticles. 26 By surface chemistry measurements and theoretical calculations, Strasser and co-workers provided a molecular level understanding of the unprecedented electrocatalytic activity for the electroreduction of oxygen on dealloyed fuel cell catalysts.…”
Section: Eff Ect Of Strain On Reactivity Of Metal Surfacesmentioning
confidence: 99%
“…11 Compressive strains and ligand effects associated with such percolated nanostructures can lead to d band broadening and lowered valence band center relative to the Fermi level. 17,19,87 It is postulated that the change in the electronic structure induced by the percolated nanoparticle structure can reduce the binding energy of oxygenated species, 16 thus lowering the activation barrier for the rate-limiting step and increasing the activity for ORR 6 relative to Pt nanoparticles. It should be mentioned that although Pt-4nm and AT-"Pt 3 Co" nanoparticles exhibit comparable coverage of oxygenated species on the positive-going scan (Figure 1b), recent DFT studies have shown that direct correlation between ORR activity and OH coverage from water activation is not straightforward.…”
Section: Sizes and Size-dependentmentioning
confidence: 99%
“…To maintain a constant d band filling, the valence band center relative to the Fermi level 17,19,87 is lowered, 20,90 which reduces the binding of surface Pt atoms toward oxygenated adsorbates. Decreased surface reactivity relative to Pt is supported by the positive shift in the onset of adsorption of oxygenated species in the voltammogram data of HT-AT-"Pt 3 Co" (Figure 1) and decreased d-band vacancy of HT-AT-"Pt 3 Co" observed from the Pt L 2, 3 edge (Figures 14 and 15) relative to AT-"Pt 3 Co" (Table 3) and Pt nanoparticles.…”
Section: Sizes and Size-dependentmentioning
confidence: 99%
“…The weak interaction of CO2 with the Pt surface is responsible for its negative, close to zero, reaction order. The decrease in the binding strength of CO adsorbed on Pt as the coverage increase [43][44][45][46] may account for the observed variation in the reaction order for CO, varying in the [-0.05, +0.14] range (Table 4), together with the negative order for H2. As far as the CO surface coverage increases, its binding energy to the Pt surface decreases and hence, the H2 inhibition of the WGS activity increases [47].…”
mentioning
confidence: 99%